A tin‐incorporated multi‐phase perovskite nanocomposite for efficiently catalyzing oxygen evolution reaction. (6th May 2022) - Kong, Ziqi; Dongyang, Biaokui; Yang, Wenying; Li, Lu; Li, Lei; Dong, Feifei; Lin, Zhan
Summary: The rational design of effective and specific catalysts for oxygen evolution reaction (OER) is of vital importance for the implementation of electrochemical water oxidation as a sustainable route to produce hydrogen. Perovskite oxides have attracted considerable interests in view of the highly tunable structural, electronic, and catalytic properties associated with their compositions. Herein, an efficient Sn‐incorporated nominal perovskite nanocomposite, SrCo0.7 Sn0.3 O3−δ (SCS), derived from a facile one‐pot self‐assembly process, is designed as an outstanding electrocatalyst to catalyze OER in alkaline conditions. Benefiting from the unique structure, increased active oxygen intermediates, and favorable electrical conductivity, the optimized SCS exhibits superior OER electrocatalytic performance, including low overpotential of only 309 mV at 10 mA cm −2, fast kinetics with a small Tafel slope of 56 mV dec −1, and 72‐fold improvement in mass activity and 108‐fold enhancement in specific activity relative to the pristine SrCoO3−δ catalyst. The SCS catalyst also demonstrates excellent OER durability with negligible potential fluctuation for 30 hours continuous operation. This work highlights a promising strategy to develop high‐performance perovskite nanocomposites to perform efficient OER electrocatalysis. Abstract : A multi‐phase nanocomposite SCS electrocatalyst is derived from a facile one‐pot self‐assembly process. Tin incorporation is in favor of crystal structure, oxygen transport, and electrical conductivity. SCS nanocomposite exhibits impressive OER activity and durability, substantially outperforming its pristine SC counterpart.